The essentials of a global index for cognitive function - Antony Joseph Mathew; Weaver Ian; Rueffer Matthew; Guthrie Najla; Evans Malkanthi (Translational Neuroscience, 2017)
Cognition is comprised of the faculties: perception, creativity, intuition, and ratiocination. Optimal levels of cognition are needed for independent functioning and balanced living. With an aging population that continues to grow, dietary supplements that tilt the balance towards maintenance of cognition are being marketed for vulnerable populations facing these challenges. Randomized clinical trials provide the causal inference necessary to define the efficacy of emerging nutraceuticals. Cognition testing, in particular, requires a battery of tests that encompass all brain regions involved in cognition so as to provide endpoints necessary for product validation. The lack of well controlled studies for comparison analyses, limited sample sizes, ambiguous dosages, and poor cognitive measures result in data that cannot be compared across studies to determine the efficacy of supplements claiming to enhance cognition. Clinical trials for the nutraceutical industry should consider the multifaceted nature of supplements, where clinical endpoints must be comprehensive while remaining feasible. Combining endpoints of cognition with physiological biomarkers of immunity and metabolism to arrive at a global index for cognitive health may be necessary for claim substantiation in order to fully justify and scientifically validate improvements in cognitive health. The issues and needs of a global index will be discussed here.